Agricultural Contracts in Mindanao: the Case of Banana and Pineapple - Larry N. Digal (Philippine Institute for Development Studies (PIDS), 2007)
Contract growing has been defined as an agreement between farmers and processing and/or marketing firms under forward agreements, usually at predetermined prices for the production and supply of agricultural products (Eaton and Shepherd 2001). As such, it offers a solution to a number of production and marketing problems that lead to low farm productivity and profitability. These problems plague the agricultural sector and contribute to the high poverty incidence in the rural sector particularly in many areas in Mindanao. On the other hand, Mindanao, being groomed as the countrys food basket, shows an example on how contract growing can address various marketing and production problems in the farm sector. This is demonstrated in industries that serve as the lifeblood of Mindanaos economy for many years such as banana and pineapple. Production of these commodities including asparagus, corn, and poultry was pioneered mainly by multinationals and large agribusiness firms in the island-region. This study aims to understand the nature of contract farming in Mindanao, identify problem areas and opportunities, and analyze its implications to Mindanaos agricultural sector particularly in terms of efficiency, equity, and sustainability. Agricultural contracts in banana and pineapple were analyzed using the principal-agent framework. The structure conduct performance (SCP) model was used to incorporate the analysis of external factors affecting the contract or the project such as demand and supply conditions as well as government policies. Primary data, which focus mainly on the contracts of bananas and pineapple, were gathered through structured interviews with key informants such as farmers or growers, contractors and relevant government agencies, and nongovernment organizations. In addition, information on external conditions affecting the performance of agricultural contracts such as government policies and socioeconomic factors were gathered.
Keywords: 330; crop production; agricultural contracts; marketing; contractual arrangements; contract growing; banana; pineapple; Vertragsanbau; Tropisches Produkt; Agrarproduktion; Marketing; Prinzipal-Agent-Theorie; Mindanao; Philippinen